Chemotherapy of the Cysticercus longicollis (metacestod of taenia crassiceps, zeder 1800). In the Mouse Mastomys Natalensis - ΧΑΡΑΛΑΜΠΙΔΗΣ Σ.; CHANDRA, S. (Journal of the Hellenic Veterinary Medical Society, 2019)
Mebendazole, cambendazole, parbendazole, praziquantel and nitrofurantoin at the daily dose of 100 mg/kg and trichlorphon of 75 mg/kg were administered to 30 mice each one of which was intraperitoneally infected with 10 Cysticercus longicollis. At the 110th day after infection each drug was given orally in 5 mice for 10 days. At the 132th day after infection (10 days after the end of the treatment) all animals were sacrificied. The evaluation of the anthelmintic effect of each drug was based on the comparison of the mass and the number of the cysticerci found in the treated animals to that of the untreated controls. The infectiveness of these cysticerci was checked by their ability to evaginate when incubated (25 of them per mouse ) in a solution of thripsin (4mg /ml) at 37°C for 4 h. Mebendazole proved to be almost 100% effective in 4 mice. Cysticerci were found in one only mouse of the mebendazole group. But even so 55,5% only of them were able to evaginate in the solution of thripsin, whereas in the control group 81% of the cysticerci they did so Although praziquantel could not reduce the number and the mass of the cysticerci it cause the cvagination of the majority of them while yet it the periotoneal cavity of the mice. As for the rest (non-cvaginated) it was found that 36,8% out of them were evaginated after post morten incubation in the solution of thripsin. The other compounds tested in these experiment failed to show any anthelmintic activity.